Risk Factors of Children with Autism Spectrum Disorder (ASD) in Palembang, Indonesia - Leonardo Satria; Ziske Maritska; Nita Parisa (Scientia Psychiatrica, 2020)
Background: Autism Spectrum Disorder (ASD) is a group of nervous system development disorders with polygenic inheritance patterns, characterized by a type of dysfunctional in social communication and limited also repetitive behaviors. Risk factors for ASD can be divided into two categories in general: genetic, and environmental factors. To date, a study about risk factors of ASD in Indonesia, let alone Palembang, is limited. Therefore, this study wished to investigate the risk factors of children with ASD in Dr. Mohammad Hoesin General Hospital, Palembang. Methods: This study is an observational descriptive study. Samples were children with ASD who went to Dr. Mohammad Hoesin General Hospital, Palembang. The primary data obtained from a semi-structured interview with parents/guardians of children with ASD, while secondary data obtained from their medical records. Results: The most common risk factors identified in this study are the paternal age and maternal age ≥ 30 years at the time of conception (59,8% and 40.2%), and the history of cesarean delivery (27,8%). Conclusion: This study concludes that the occurrence of ASD in Palembang is multifactorial, involving both genetic and environmental risk factors.